2023
DOI: 10.21203/rs.3.rs-2435059/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of high proprotein convertase subtilisin/kexin type 9 antibody level with poor prognosis in patients with diabetes: A prospective cross-sectional study

Abstract: Background In addition to pathogenic autoantibodies, polyclonal autoantibodies with unknown physiological roles and pathogenicity are produced in the body. Moreover, serum antibodies against the proprotein convertase subtilisin/kexin type 9 (PCSK9) protein, which is integral to cholesterol metabolism, have also been observed. Therefore, we aimed to examine the clinical significance of PCSK9 antibody (PCSK9-Ab) levels. Methods We measured blood PCSK9-Ab and PCSK9 protein levels in 109 healthy donors (HDs) and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…After 48 months, it was observed that Evolocumab effectively brought down LDL-C to an average of 30 mg/dL which was sustained in subsequent studies. Although a recent clinical study argued that after examining all potential confounding factors, higher levels of anti-PCSK9 autoantibodies were significantly related to the increased deaths among diabetes patients, 451 Evolocumab has been reported to significantly decrease the risk of recurring CVEs in patients with pre-existing ASCVD and/or T2D. 452,453 The relative risk (RR) for the main outcome reduced by 15%, with a HR of 0.85 (95% CI 0.79-0.92) over a median 2.2-year monitoring period.…”
Section: Strategies Of the Development Of Emerging Pcsk9 Inhibitorsmentioning
confidence: 99%
“…After 48 months, it was observed that Evolocumab effectively brought down LDL-C to an average of 30 mg/dL which was sustained in subsequent studies. Although a recent clinical study argued that after examining all potential confounding factors, higher levels of anti-PCSK9 autoantibodies were significantly related to the increased deaths among diabetes patients, 451 Evolocumab has been reported to significantly decrease the risk of recurring CVEs in patients with pre-existing ASCVD and/or T2D. 452,453 The relative risk (RR) for the main outcome reduced by 15%, with a HR of 0.85 (95% CI 0.79-0.92) over a median 2.2-year monitoring period.…”
Section: Strategies Of the Development Of Emerging Pcsk9 Inhibitorsmentioning
confidence: 99%
“…In terms of biomarker species, studies have reported enzyme, antigen, and, in recent years, nucleotide markers (1-3). However, there are still some reports on antibody markers, which include heat-shock 60-kD protein 1 (4), replication protein A2 (5), programmed cell death 11 (6), metalloproteinase 1, chromobox homolog 1, chromobox homolog 5 (7), DnaJ heat shock protein family (Hsp40) member C2 (8), adaptor-related protein complex 3 subunit delta 1 (9), serpin peptidase inhibitor, clade E member 1 (10), death-inducer obliterator 1, cleavage and polyadenylation specificity factor 2, forkhead box J2 (11) and thiosulfate sulfurtransferase-like domain-containing 2 (12) for acute ischemic stroke (AIS); ATPase, Ca ++ transporting, plasma membrane 4 (10), bone morphogenetic protein 1 (3,13), deoxyhypusine synthase (14), SH3 domain-binding protein 5 (15), prolyl carboxypeptidase (16), low-density lipoprotein receptor-related protein-associated protein 1 (17) and additional sex combs-like 2 (18) for atherosclerosis; nardilysin (19) for acute cardiac syndrome; and insulin (20), glutamic acid decarboxylase (21), adiponectin (22) and growth arrest and DNA-damage-inducible gene 34 (23,24), and proprotein convertase subtilisin/kexin type 9 (25) for diabetes mellitus (DM).…”
Section: Introductionmentioning
confidence: 99%